Dogfight [videorecording (Blu-Ray)] - Comfort, Bob; Phoenix, River; Taylor, Lili; Panebianco, Richard, 1971-; Clark, Anthony, 1964-; Whitfield, Mitchell, 1969-; Daily, E. G.; Near, Holly; Bukowski, Bobby; Daring, Mason (Criterion collection, 2024)
An ineffably bittersweet portrait of youth in the 1960s, Nancy Savoca's funny, sensitive tale of love and war etches two vividly alive characters: aspiring San Francisco folk singer Rose and hotheaded, Vietnam-bound marine Eddie, who meet on the occasion of a cruelly misogynistic party where men compete to bring the most unattractive dates they can find. But what begins as a night to forget unexpectedly develops into something far more meaningful. -- container